Profile of Elderly COVID-19 Patients at Indrapura Field Hospital, Surabaya - Mahdian, Haidar; Triyono, Erwin Astha; Handajani, Noor Idha; Kartina, Leny (Universitas Airlangga, 2025)
Highlights: Elderly patients with comorbidities are more vulnerable to coronavirus disease (COVID-19) because it can cause a higher mortality rate and a poor prognosis. Most of the elderly COVID-19 patients who were given symptomatic treatment were cured. Abstract Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a pathogen that causes coronavirus disease (COVID-19). The elderly, especially those with comorbidities, are vulnerable to COVID-19. This study aimed to determine the profile of elderly patients with COVID-19 and to provide valuable data for further research. Methods: This was a retrospective descriptive study of 132 (n=132) elderly COVID-19 patients at Indrapura Field Hospital, Surabaya, between April and October 2021. The clinical profile was determined by collecting medical record data from Indrapura Field Hospital, Surabaya. All statistical data analyses were conducted using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) for Macintosh version 25.0. Results: This study indicated that among 132 (n=132) elderly patients, the predominated age range was 61–63 years old (37.12%), and most of the patients were males (57.6%). The majority of the patients' occupations were private employees, and hypertension was the main comorbidity in elderly patients (52.3%). Most patients experienced mild symptoms (46.2%), with the most common complaint being a productive cough (42.4%). All of the patients had no antiviral, antibacterial, or corticosteroid therapy. There were 73 patients (55.3%) who had been hospitalized for less than 10 days, with most of the patients (78.79%) cured and allowed to go home. Conclusion: The majority of patients at Indrapura Field Hospital, Surabaya, were elderly male patients, with hypertension being the most common comorbidity. Most patients exhibited mild symptoms, mainly a productive cough, and showed significant improvement with symptomatic, isolation, relaxation, nutrition, and observation (SIRNO) therapy, resulting in a high recovery and discharge rate.